Compartmentalization, adaptive evolution and therapeutic response of HIV-1 in the gastrointestinal tract (GIT) of African patients infected with Subtype C: implications for the enhancement of therapeutic efficacy - Cassol, Sharon (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2014.